Implementasi Kelas Akselerasi Dalam Pembelajaran Pendidikan Agama Islam (PAI) di SMA Negeri 1 Kediri - Mastun Nisa', Dwi Haris (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
The article is intended to describe the implementation and the supporting factors of Islamic education at accelerated classes at state SMA 1 Kediri. Descriptive-qualitative was employed, and the data were elicited through interview, observation, and documentation. It was found out that the implementation of Islamic education at accelerated classes was not very much different from the regular classes in the form of curriculum, methods, and evaluation. The difference is only that accelerated classes are only for gifted and talented students. In addition, some supporting factors were good communication as well close relationship between the teachers and students, skilled teachers, sufficient facilities, good students, students’ illiterate technology, KMP. Some barriers were also found. They are teachers’ literate technology, small classes, and students’ minimum religious background. Therefore, any party related to this should contribute to overcome the barriers.